Anti-Jamming Algorithm for Detection of QRS and ST Segments on Electrocardiogram; MATEC Web of Conferences; Vol. 79 : Information-Measuring Equipment and Technologies (IME&T 2016) - Overchuk K. Kirill (2016, 2016)
Title screen